Cowards and Heroes: Group Loyalty in the American Civil War - Costa, D. L.; Kahn, M. E. (Quarterly Journal of Economics, 2003)
What motivated men to risk death in the most horrific war in U. S. history when pay was low and irregular and military punishment strategies were weak? In such a situation creating group loyalty by promoting social capital is of paramount importance and in the Civil War was the cement of both armies. We find that individual and company socioeconomic and demographic characteristics, ideology, and morale were important predictors of group loyalty in the Union Army. Company characteristics were more important than ideology or morale. Soldiers in companies that were more homogeneous in ethnicity, occupation, and age were less likely to shirk.